PERAN PENDIDIKAN SEBAGAI PENGIKAT KEBERAGAMAAN DAN PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA DESA LEMBUR KECAMATAN LEMBUR KABUPATEN ALOR: PERAN PENDIDIKAN SEBAGAI PENGIKAT KEBERAGAMAAN DAN PENINGKATAN KAPASITAS SUMBER DAYA MANUSIA DESA LEMBUR KECAMATAN LEMBUR KABUPATEN ALOR - Saetban, Anton; Petrus M.T. Dony; Nehemia Fanpada; Yermia Wabang; Jon A.L. Yame (Institut Agama Kristen Negeri Kupang, 2023)
Indonesia consists of various tribes spread across several islands, in the midst of this globalization era, westernization is considered one that has faded local cultural values because many western values have been diffused into local values. The progress of a nation is influenced by the quality of education of the nation itself because higher education can produce quality human resources. The education referred to here is not non-formal but formal in nature, covering the teaching and learning process which involves teachers and students. The purpose of this PKM activity is to prepare students to be able to develop cooperative networks in an effort to solve problems to meet the needs of the dynamics of life in society while at the same time educating the nation's life in advancing the welfare of society, especially the people of Alor Regency.